Investigation Of The Relationship Between Watching Programs Of Sabalan Channel And Social Capital Of Ardebil Citizens - Amirpoor, Ali; Jafari, Ali (The Turkish Online Journal of Design Art and Communication, 2016)
Objective: This study aimed to investigate the relationship between the social capital citizens Ardebil Sabalan channel to watch the surveying method is done. Methods: This study is a survey using multistage cluster sampling was conducted schema. The population of this research was all Citizens over 20 years of Ardebil, of which 400 were selected through Cochran's formula. Findings: correlation obtained to examine the relationship between the variables showed that applications Sabalan channel direct correlation between social capital and social trust inverse correlation with Solidarity with political participation informal social ties inverse correlation, with correlation faith-based engagement there is an inverse correlation with equity directly and civic participation. However, the correlation between the uses of Sabalan channel programs with Participation and civic leadership, giving & volunteering, diversity friendship groups. Conclusion: Sabalan channel as one of the factors of socialization in the province of Ardebil, play an important role in the institutionalization of values, norms and social cohesion between the local and national audiences and a total increase of the social capital citizens Ardebil.
Keywords: social capital; media; network Sabalan; Citizens Ardebil; sosyal sermaye; medya; ağ Sabalan; Vatandaşlar Erdebil